Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica. Issue 12 (7th December 2016) - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C.; Firing, Yvonne
Abstract: Ice shelves around Antarctica are vulnerable to an increase in ocean‐driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice‐shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice‐shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation‐rate‐based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin‐Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting. Key Points: We present the turbulent kinetic energy and thermal variance dissipation rates beneath an ice shelf for the first time The highest thermal variance dissipation rate is found near the ice/ocean interface The highest turbulent kinetic energy dissipation rate is found near the grounding line